MANAJEMEN WALET MUDA FUTSAL AKADEMI KABUPATEN KEBUMEN TAHUN 2012/2013 - Heri Siswanto (Universitas Negeri Semarang, 2015)
The purpose of this study is to describe how the management process Walet Muda Futsal Academy runs . Research methods used include interviews , observation and documentation. Results of this study are organizational management stewardship , management and handling athlete management coaches in the Walet Muda Futsal Academy have said well . Management infrastructure and management supervisor at Young Swallow Futsal Academy has not been going well . Overall management process Walet Muda Futsal Academy could not be said better. Conclusions of the research results suggested some of the following : (1 ) Walet Muda Futsal Academy as soon as a new recruit competent in the field of organization and coaches , so there is no administrator or coach who doubles duty . ( 2 ) Walet Muda Futsal Academy should pay more attention to the environment in which athletes hang out , athletes' health and nutritional intake in order to maintain the concentration of athletes and fitness athletes . ( 3 ) management of facilities and infrastructure must be managed properly , from the procurement of new facilities and infrastructure , usage , maintenance , record keeping , providing a reserve fund for the infrastructure needs of the sudden . Make comparisons with infrastructure in other places in order to be used as a reference in the provision of next.